ANALISA PERCEPATAN WAKTU PADA PROYEK PEMBANGUNAN STRUKTUR GEDUNG LABORATORIUM UNPATTI MENGUNAKAN METODE CRASHING PROGRAM DAN FAST-TRACK - Christian Salakory; Octovianus Jamlaay; Henriette Dorothy Titaley (Jurusan Teknik Sipil, 2023)
The development project of the Masela Block Supporting Intergrated Laboratory, Pattimura University was intended to be the object of this research because it was based on the problems that occurred in the project, namely delays. Based on secondary data obtained from the project, the budget plan (RAB) and time schedule are used the duration and normal costs of the project. Then crashing program method and the fast-track method are applied to reduce the duration and find out the total cost needed so that the project can run properly as the planned target time and does not experience delays. Crashing and fast-track methods are methods use to accelerate the execution time in contruction projects. Although these two methods can clearly reduce the application of these two methods on project implementation costs. From the analysis result carried out on structural work that crosses the critical path, it is obvious that the crashing time method is reduced by 17% or 38 days and the resulting cost overrun is 0.02% or IDR 10,615,733.38, while for the fast-track method reduced work duration is around 18% or 41 days where the project cost is also reduced by 1.89% or IDR 774,757,772.32 from the normal duration which should be 225 days at a cos of IDR 62,257,321,000.00.